2000
DOI: 10.1046/j.1432-1327.2000.01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of the platelet Na+/H+ exchanger by trimeric G‐proteins

Abstract: Human platelets contain a Na 1 /H 1 exchanger (NHE) that regulates the cytosolic pH. The role of trimeric G-proteins in NHE control was investigated in plasma membrane vesicles by measuring exchange of intravesicular protons for extravesicular Na 1 . Exchange was saturable, independent of membrane potential and inhibited by ethylisopropyl amiloride (K i 0.05 mmol´L 21 ), demonstrating the involvement of NHE-1. The G-protein activators AlF 4 2 and GMP-P(NH)P reduced exchange by increasing the K m for Na 1 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A rise in intracellular Na 1 may reverse the Na 1 /Cl --dependent noradrenaline transporter and induce carrier-mediated neurotransmitter release. H 3 R activation reduces NHE activity in sympathetic nerve terminals, leading to inhibition of noradrenaline release in myocardial ischemia (Silver et al, 2001); the mechanism is not fully understood, although a direct Ga i/o subunit/NHE interaction appears likely (van Willigen et al, 2000).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…A rise in intracellular Na 1 may reverse the Na 1 /Cl --dependent noradrenaline transporter and induce carrier-mediated neurotransmitter release. H 3 R activation reduces NHE activity in sympathetic nerve terminals, leading to inhibition of noradrenaline release in myocardial ischemia (Silver et al, 2001); the mechanism is not fully understood, although a direct Ga i/o subunit/NHE interaction appears likely (van Willigen et al, 2000).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…The intracellular acidosis during myocardial ischemia may activate the sarcolemmal NHE-1 with subsequent Na ϩ influx, cytosolic Ca 2ϩ overflow, and ischemic contracture. Because NHE-1 is negatively regulated by inhibitory G proteins (G i␣ ), 35 it is possible that it may also contribute to the inhibition of ischemic contracture by EP 3 overexpression. In addition, Zacharowski and coworkers 36 reported that the inhibition of mitochondrial K ATP channels by 5-hydroxydecanoic acid counteracts the cardioprotection by EP 3 receptor agonists, but the role of K ATP for prostaglandinmediated cardioprotection is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Second, H3R activation can reduce neurotransmitter release by inhibiting N- and P/Q-type voltage-gated calcium channels again through the Gβγ subunit ( 68 , 69 ). Third, H3R activation has been shown to reduce the activity of the sodium–proton exchanger (NHE), which is under the control of Gαi ( 70 , 71 ). Therefore, activation of H3R has opposite effects on neuronal activity to that of H1R or H2R activation.…”
Section: Histamine Receptor Signalingmentioning
confidence: 99%